Proposed new design for Az-Zahrah Wellness Centre at Lot 18, Jalan Diplomatik 3, Precint 15, 62050, Putrajaya / Nurul Najwa Dalila Mastor - Mastor, Nurul Najwa Dalila (Faculty of Architecture, Planning and Surveying, 2010)
The final project for student semester 6, Diploma In Interior Architecture is actually to give out all the input that the student gain trough out from the first semester until internship training about interior design. The project that had been chosen for the final project is proposed new design for Az-Zahrah Wellness Centre at lot 18, Jalan Diplomatik 3, Precint 15, 62050 Putrajaya. This proposed of wellness centre is actually to attract muslim women since this wellness centre is open to only female, to try for themselves the medical spa that provided under the supervision of doctors, fitness class on daily exercise and healthy eating habit. They also provide hair and beauty salon services to customers as to give the full sets of beauty in healthiness. The target market for the user of this wellness centre is muslim women from all age and medium high classes that concern about beauty trough their inner and outer look and appearance in a healthy lifestyle, not forgetting to those who is finding a way of rejuvenating themselves in recovering from chronic disease. As the customers that comes to the wellness centre is from medium high class, each room and services space should match the customer’s need and comfort while attending treatment session. The concept and image that had been chosen for the interior must meet the client requirement to reflect the client itself to their customers to gain their faith and good impression on the services provided as well as the impact of first impression on the design that serves comfort to the customers. Besides the client and customers, faith from staff and workers is also important in doing design so that the environment of work space is making them in comfort to provide good services. In terms of that, the design style that best suit for Az-Zahrah Wellness Centre is based on Modern Contemporary medical spa, which goes all the way with the client requirement as they were based on medical institution under Pusat Rawatan Islam Az-Zahrah (AZIM). Before going far with getting desire design concept, a number of data analysis should be done as to identify on types of customers range to attend the treatment session, types and brand of the product provided types of services that are offered, space to be concluded in the proposed services area, operation time and management of the wellness centre, as well as working and services flow for staff and customers. In doing the research, information can be gain from many sources such as trough interview, internet, printed media, observation as both from local or international.